Efeito da heterogeneidade ambiental sobre a estrutura de comunidades. - Ortega, Jean Carlo Gonçalves (2017)
Studies commonly report positive correlations between environmental heterogeneity and aspects of community structure, such as species richness and beta diversity. However, evidence suggesting no effect or negative relationships are also observed. The effect of environmental heterogeneity on species richness was evaluated in different ecosystems, taxonomic groups, spatial scales and experimental designs by a systematic review and meta-analysis. A positive effect of environmental heterogeneity on species richness was observed, do not depend of differences in experimental designs, spatial scales, taxonomic groups, type of ecosystem or the type of environmental heterogeneity measured. However, the evaluated experiments do not seek to understand processes underlying this relationship between environmental heterogeneity and species richness. The effect of niche and neutral processes on fish species composition variation in macrophytes stands in the Cuiabá River floodplain lakes was evaluated and whether the relationship changes according to the spatial scale considered. The effect of proxy variables of neutral (species richness), niche (environmental heterogeneity) and isolation (distance from pond to river) process on beta diversity was also evaluated. Environmental heterogeneity negatively correlated to beta diversity only on a larger spatial scale. Isolation correlated positively with beta diversity. The results suggest that processes related to beta diversity change according to the spatial scale considered. While neutral sampling effects operate on a small scale, niche processes and dispersion operate at larger spatial scales.